Ryanodine and inositol trisphosphate receptors coexist in avian cerebellar Purkinje neurons (The Rockefeller University Press, 1991)
Two intracellular calcium-release channel proteins, the inositol trisphosphate (InsP3), and ryanodine receptors, have been identified in mammalian and avian cerebellar Purkinje neurons. In the present study, biochemical and immunological techniques were used to demonstrate that these proteins coexist in the same avian Purkinje neurons, where they have different intracellular distributions. Western analyses demonstrate that antibodies produced against the InsP3 and the ryanodine receptors do not cross-react. Based on their relative rates of sedimentation in continuous sucrose gradients and SDS-PAGE, the avian cerebellar InsP3 receptor has apparent native and subunit molecular weights of approximately 1,000 and 260 kD, while those of the ryanodine receptors are approximately 2,000 and 500 kD. Specific [3H]InsP3- and [3H]ryanodine-binding activities were localized in the sucrose gradient fractions enriched in the 260-kD and the approximately 500-kD polypeptides, respectively. Under equilibrium conditions, cerebellar microsomes bound [3H]InsP3 with a Kd of 16.8 nM and Bmax of 3.8 pmol/mg protein; whereas, [3H]ryanodine was bound with a Kd of 1.5 nM and a capacity of 0.08 pmol/mg protein. Immunolocalization techniques, applied at both the light and electron microscopic levels, revealed that the InsP3 and ryanodine receptors have overlapping, yet distinctive intracellular distributions in avian Purkinje neurons. Most notably the InsP3 receptor is localized in endomembranes of the dendritic tree, in both the shafts and spines. In contrast, the ryanodine receptor is observed in dendritic shafts, but not in the spines. Both receptors appear to be more abundant at main branch points of the dendritic arbor. In Purkinje neuron cell bodies, both the InsP3 and ryanodine receptors are present in smooth and rough ER, subsurface membrane cisternae and to a lesser extent in the nuclear envelope. In some cases the receptors coexist in the same membranes. Neither protein is observed at the plasma membrane, Golgi complex or mitochondrial membranes. Both the InsP3 and ryanodine receptors are associated with intracellular membrane systems in axonal processes, although they are less abundant there than in dendrites. These data demonstrate that InsP3 and ryanodine receptors exist as unique proteins in the same Purkinje neuron. These calcium-release channels appear to coexist in ER membranes in most regions of the Purkinje neurons, but importantly they are differentially distributed in dendritic processes, with the dendritic spines containing only InsP3 receptors.